2006
DOI: 10.1590/s1516-31802006000100010
|View full text |Cite
|
Sign up to set email alerts
|

High prevalence of morphological subtype FAB M1 in adults with de novo acute myeloid leukemia in São José dos Campos, São Paulo

Abstract: CONTEXT AND OBJECTIVE: Geographical variations have been described in acute myelogenous leukemia (AML). In Brazil, few studies have been published on this. The aim of this study was to demonstrate the high prevalence of French-American-British (FAB) M1 subtype in adults with de novo AML in São José dos Campos, State of São Paulo, Brazil. DESIGN AND SETTING: Retrospective analysis, at Hospital Pio XII in São José dos Campos, a public non-teaching institution. METHODS: Records from 39 consecutive adult patients … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
6
0

Year Published

2011
2011
2019
2019

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(8 citation statements)
references
References 3 publications
2
6
0
Order By: Relevance
“…Rego et al [6] found completely different percentages of APL in two different cities within Table 3 Lineage demarcation markers expression in acute leukemia Brazil (7.8 and 21% of AML). Most published data indicated the predominance of M1-2 as the most common AML subtypes [5,[9][10][11]. In the current study, the commonest FAB AML subtype was AML-M4/5 (34.5%) and this was in concordance with other published studies who reported marked predominance of M4/5 subtypes varying between 42.2 and 73% of AML cases [4,8].…”
Section: Leukemia Subtypessupporting
confidence: 92%
See 2 more Smart Citations
“…Rego et al [6] found completely different percentages of APL in two different cities within Table 3 Lineage demarcation markers expression in acute leukemia Brazil (7.8 and 21% of AML). Most published data indicated the predominance of M1-2 as the most common AML subtypes [5,[9][10][11]. In the current study, the commonest FAB AML subtype was AML-M4/5 (34.5%) and this was in concordance with other published studies who reported marked predominance of M4/5 subtypes varying between 42.2 and 73% of AML cases [4,8].…”
Section: Leukemia Subtypessupporting
confidence: 92%
“…In our study, APL accounted for 23%, while non-APL AML accounted for 77% of all AML cases. Most of the previous studies reported lower APL percentages ranging from 5 to 14% of all AML cases [7][8][9][10][11] while fewer investigators stated nearly similar percentage to our results (24%) [4,5]. Rego et al [6] found completely different percentages of APL in two different cities within Table 3 Lineage demarcation markers expression in acute leukemia Brazil (7.8 and 21% of AML).…”
Section: Leukemia Subtypessupporting
confidence: 73%
See 1 more Smart Citation
“…18 In São José dos Campos (state of São Paulo), there was higher prevalence of the M1 subtype, followed by M2. 37 In Rio de Janeiro, there was higher frequency of M2, followed by M3 and M4, which were equally frequent, 31 while in Rio Grande do Sul, higher frequency of M2 was found, followed by M1. 32 In the present study, the increased incidence of the FAB subtype M0 was based on samples obtained from a single institution.…”
mentioning
confidence: 88%
“…In the current series we found a higher frequency of the M3 subtype and this finding is similar to that reported for Brazilian patients. (21-24) During the study period, there were only seven reported cases of ALL, thus preventing a more detailed analysis.…”
Section: Discussionmentioning
confidence: 99%